'What do you think it is that makes them who they are'? The connections between Latinx stereotypes, claims of white difference, and characters' deaths in Breaking Bad. (September 2021) - Bernhardt, Mark
This article argues that while reliant on Latinx stereotypes in character construction, Breaking Bad (2008–2013) ultimately uses them to problematise American racial categories and conquest mythology. Comparing stereotyped Latinx criminals to the main white character, Walter White (Bryan Cranston), who claims difference, reveals that they share traits. In its use of Latinx stereotypes to transfer focus from difference to sameness, Breaking Bad shifts the imperial gaze to offer a critical view of the regeneration through violence myth, so integral to American western expansionism and central in Walt's story, in that he dies in his attempt to regenerate by killing his Latinx enemies.